Supraclavicular Flap Reconstruction of Cutaneous Defects Has Lower Complication Rate than Mucosal Defects - Kadakia, Sameep; Agarwal, Jay; Mourad, Moustafa; Ashai, Sara; Lee, Thomas; Ducic, Yadranko (Journal of Reconstructive Microsurgery, 2017)
Background The objective of this study was to determine whether there was a difference in complication rate between cutaneous and mucosal defects reconstructed with the supraclavicular artery flap.Methods Retrospective review of postoperative complications in 63 patients from 2008 to 2015 with cutaneous and mucosal head and neck defects following oncologic ablation reconstructed with the supraclavicular flap, with a minimum follow-up duration of 6 months. Of the 63 patients, 38 patients had cutaneous defects, whereas 25 had mucosal defects. Patients were followed up postoperatively to determine the presence of wound infection, partial flap necrosis, complete flap necrosis, and fistula formation. Complications in both defect groups as well as a statistical comparison of total complications were analyzed.Results Patients with cutaneous defects reconstructed with the supraclavicular flap had significantly lower postoperative complications than those with mucosal defects (p = 0.002). Flap necrosis, both partial and complete, was also lower in this same group (p = 0.0052).Conclusion The supraclavicular artery flap may be a more suitable option for patients with cutaneous defects, given the reliability and lower propensity for postoperative complicationsLevel of Evidence The level of evidence is 4.
Keywords: supraclavicular; complications; island flap